Coreless Fiber‐Based Whispering‐Gallery‐Mode Assisted Lasing from Colloidal Quantum Well Solids. (4th November 2019) - Sak, Mustafa; Taghipour, Nima; Delikanli, Savas; Shendre, Sushant; Tanriover, Ibrahim; Foroutan, Sina; Gao, Yuan; Yu, Junhong; Yanyan, Zhou; Yoo, Seongwoo; Dang, Cuong; Demir, Hilmi Volkan
Abstract: Whispering gallery mode (WGM) resonators are shown to hold great promise to achieve high‐performance lasing using colloidal semiconductor nanocrystals (NCs) in solution phase. However, the low packing density of such colloidal gain media in the solution phase results in increased lasing thresholds and poor lasing stability in these WGM lasers. To address these issues, here optical gain in colloidal quantum wells (CQWs) is proposed and shown in the form of high‐density close‐packed solid films constructed around a coreless fiber incorporating the resulting whispering gallery modes to induce gain and waveguiding modes of the fiber to funnel and collect light. In this work, a practical method is presented to produce the first CQW‐WGM laser using an optical fiber as the WGM cavity platform operating at low thresholds of ≈188 µJ cm −2 and ≈1.39 mJ cm −2 under one‐ and two‐photon absorption pumped, respectively, accompanied with a record low waveguide loss coefficient of ≈7 cm −1 and a high net modal gain coefficient of ≈485 cm −1 . The spectral characteristics of the proposed CQW‐WGM resonator are supported with a numerical model of full electromagnetic solution. This unique CQW‐WGM cavity architecture offers new opportunities to achieve simple high‐performance optical resonators for colloidal lasers. Abstract : A novel whispering‐gallery‐mode (WGM) assisted optical resonator is demonstrated for lasing of colloidal quantum wells (CQW). The CQW‐WGM resonator benefits from a high net modal gain coefficient of core/crown@gradually alloyed shell (C/C@GAS) CQWs solids. WGM‐assisted laser of close‐packed films of C/C@GAS nanoplatelets addresses the previous issues of in solution WGM lasers by performing highly stable laser emission.